Investigating novice English Language teachers’ competency : a case study / Johan @ Eddy Luaran and Nursyuhada Zakaria - Luaran, Johan @ Eddy; Zakaria, Nursyuhada (ACRULeT, Faculty of Education & UiTM Press, 2013)
Teacher competency is an important issue in the fi eld of teacher education. To be a competent teacher, an individual should possess adequate knowledge and skills to teach students in classrooms. Hence, this study aimed to investigate novice English language teachers’ competency to teach in schools. There were three research objectives which were: to identify novice English language teachers’ level of teaching knowledge, to assess their competency in classroom teaching and to assess their competency in relation to teaching knowledge and classroom teaching. This research employed a descriptive research design. A total of forty-one novice English language teachers in secondary schools were selected as the sample for the study. The instruments used were the Teaching Knowledge Test (TKT), teaching observation form and semi-structured interviews. All forty-one respondents were required to complete the TKT, while only nine respondents were selected for the observations and interviews based on their scores in the TKT. The fi ndings revealed that the novice English language teachers had adequate teaching knowledge, as refl ected in their scores in TKT. However, the knowledge was not completely applied in their teaching as observed by the researcher, which also indicated that they were incompetent in some aspects of teaching, such as choosing appropriate teaching methods and in time management. The fi ndings hoped to provide input to the teacher training programmes offered in Malaysia.